Empowerment and Self Direction Relative to the Design and Governance of Personalized Service Arrangements - Kendrick, Michael (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
The attempt to create services that are designed and directed by service users has been growing in prominence in many human service sectors and has spawned a wide variety of policies, systems and examples in many jurisdictions. This article has a focus on how decision-making and of this kind can be operationalized by demonstrating how organizational authority can be transferred to and employed by service users and their allies both singly and in conjunction with other parties. It describes various levels of empowerment relative to service decision making as well as the common organizational forms that user directed services have taken to-date.